Chiral Thiazolidine based Organocatalysts: Synthesis and Application in Asymmetric Aldol Reactions - Félix, Ana Rita G. (2020)
Several novel chiral organocatalysts derived from thiazolidines containing amide and thioureia functionalities were synthesized in good yields. These organocatalysts were tested in the asymmetric aldol reaction of acetone with p-nitrobenzaldehyde. Reaction parameters such as reaction time, catalyst loading and solvent were optimized. Products with conversions up to 84% and enantiomeric ratios (er) up to 84.5:15.5 (R:S) were obtained. The effect of several chiral and non-chiral additives on the reactivity and selectivity of the reaction was also evaluated. The reaction was extended to other aromatic aldehydes with the best organocatalyst and when p-bromobenzaldehyde was used, an er of 94.5:5.5 (R:S) was obtained.